Conbercept improves macular microcirculation and retinal blood supply in the treatment of nonischemic branch retinal vein occlusion macular edema. Issue 12 (21st November 2022) - Huang, Yikeng; Linghu, Minli; Hu, Weiwen; Huang, Xionggao
Abstract: Purpose: To investigate the effect of conbercept on macular microvascular system and retinal blood supply in the treatment of nonischemic branch retinal vein occlusion macular edema (BRVO‐ME). Methods: Patients were divided into three groups: group A (containing 12 nonischemic BRVO‐ME eyes), group B (containing contralateral 12 healthy eyes), and group C (containing 30 cataract eyes to obtain normal aqueous humor cytokine levels). Group A received monthly intravitreal injections of conbercept for 3 months. General data and best‐corrected visual acuity (BCVA) were compared among the three groups. Optical coherence tomography angiography (OCTA) results (including central macular thickness [CMT], retinal vascular density and perfusion, and foveal avascular zone [FAZ]) at baseline were compared among groups A and B. Aqueous humor cytokine levels (including VEGF, IL‐8, PDGF‐AA, TNF‐α, and ANGPTL‐4) at baseline were compared between groups A and C. Moreover, BCVA, OCTA results, and aqueous humor cytokine levels of group A before and after conbercept treatment were compared. Result: At baseline, group A had a significantly worse BCVA, lower retinal vascular density and perfusion, and numerically larger CMT and FAZ area comparing to the group B, and had a higher aqueous cytokine level (IL‐8, VEGF, and ANGPTL‐4) comparing to the group C (all p s < 0.05). After the injection of conbercept, group A presented a better BCVA (at initial diagnosis vs. after three conbercept injections: 1.16 ± 0.51 vs. 0.81 ± 0.30, logMAR, p  < 0.05), higher retinal vascular density (11.56 ± 4.73 vs. 15.88 ± 2.31, mm −1, p  < 0.05) and perfusion (0.28 ± 0.12 vs. 0.39 ± 0.06, mm 2, p  < 0.05), smaller CMT (504.92 ± 184.11 vs. 219.83 ± 46.63, mm 2, p  < 0.05), as well as a lower levels of VEGF (before first injection vs. before third injection: 113.84 [70.81, 235.4] vs. 3.94 [3.56, 8.07], pg/ml, p  < 0.05) and ANGPTL‐4 (45, 761 [7327.5, 81, 402.5] vs. 25, 015.5 [6690, 43, 396], pg/ml, p  < 0.05). However, the average FAZ area of group A expanded (at initial diagnosis vs. after three conbercept injections: 0.41 ± 0.14 vs. 0.62 ± 0.36, mm 2, p  < 0.05). Conclusion: This study demonstrated that intraocular injection of conbercept could effectively improve macular microcirculation and increase retinal blood supply in the treatment of nonischemic BRVO‐ME based on the combination of visual acuity, OCTA parameters, and aqueous humor cytokine assay results. However, further study with a larger sample size and longer observation period is still needed in the future. Abstract : With the widespread use of anti‐VEGF agents, it has become a hot issue of clinical concern whether anti‐VEGF therapy would induce or aggravate macular ischemia. This study demonstrated that intravitreal injection of conbercept could effectively improve macular microcirculation and increase retinal blood supply in the treatment of nonischemic BRVO‐ME based on the combination of visual acuity, OCTA parameters, and aqueous humor cytokine assay results.